Insight Between the Epigenetics and Transcription Responding of Cotton Hypocotyl Cellular Elongation Under Salt-Alkaline Stress - Rui, Cun; Zhang, Yuexin; Fan, Yapeng; Han, Mingge; Dai, Maohua; Wang, Qinqin; Chen, Xiugui; Lu, Xuke; Wang, Delong; Wang, Shuai; Gao, Wenwei; Yu, John Z.; et al. (Frontiers in Plant Science, 2021)
Gossypium barbadense is a cultivated cotton not only known for producing superior fiber but also for its salt and alkaline resistance. Here, we used Whole Genome Bisulfite Sequencing (WGBS) technology to map the cytosine methylation of the whole genome of the G. barbadense hypocotyl at single base resolution. The methylation sequencing results showed that the mapping rates of the three samples were 75.32%, 77.54%, and 77.94%, respectively. In addition, the Bisulfite Sequence (BS) conversion rate was 99.78%. Approximately 71.03%, 53.87% and 6.26% of the cytosine were methylated at CG, CHG and CHH sequence contexts, respectively. A comprehensive analysis of DNA methylation and transcriptome data showed that the methylation level of the promoter region was a positive correlation in the CHH context. Saline-alkaline stress was related to the methylation changes of many genes, transcription factors (TFs) and transposable elements (TEs), respectively. We explored the regulatory mechanism of DNA methylation in response to salt and alkaline stress during cotton hypocotyl elongation. Our data shed light into the relationship of methylation regulation at the germination stage of G. barbadense hypocotyl cell elongation and salt-alkali treatment. The results of this research help understand the early growth regulation mechanism of G. barbadense in response to abiotic stress.